The Influence of Managerial Supervision on Service Quality at Tryas Hotel Cirebon - Trisnawati, Iis; Supriana, Nana; Mufti, Imas (Strata International Journal of Social Issues, 2025)
The hospitality industry plays a pivotal role in Indonesia’s economic recovery by delivering services that directly influence guest satisfaction and organizational competitiveness. Within this sector, managerial supervision functions as a critical mechanism to ensure service consistency, employee discipline, and alignment with organizational objectives. This study investigates the influence of managerial supervision on service quality at Tryas Hotel Cirebon. A quantitative-descriptive analytic method was employed, involving 30 respondents selected through simple random sampling from a population of 42 hotel guests. Data were collected using structured observations, interviews, and questionnaires, and subsequently analyzed using Pearson’s product–moment correlation and t-tests at a 5% significance level. The results revealed that managerial supervision was categorized as “fairly good,” with an achievement level of 73.68%. Among the indicators, objective and precise supervision scored the highest, while goal-oriented supervision was rated the lowest. Statistical analysis demonstrated a strong and significant correlation (r = 0.761) between managerial supervision and service quality, with managerial supervision contributing 57.91% to service quality improvement. These findings highlight the necessity for hotel management to enhance supervisory practices by prioritizing goal alignment, objectivity, and continuous feedback. Strengthening these aspects is expected to foster employee performance improvements and elevate overall service quality in the hospitality sector.